2004
DOI: 10.1111/j.1745-4530.2004.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐phase Modeling and the Quality of Soybean Seeds Dried in a Counter‐current Moving Bed Drier

Abstract: The purpose of the present work is to study the simultaneous heat and mass transfer between air and soybean seeds in a countercurrent moving bed dryer, based on the application of a two‐phase model to the drying process. The numerical solution of the model is obtained by using a computational code based on backwards differential formulae. The experimental data of air humidity and temperature and of seed moisture content and temperature at the dryer outlet are compared to the simulated values, showing a good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Lacerda et al [5] studied the influence of drying variables on the quality of soybean seeds. These authors worked with a countercurrent sliding-bed dryer and proposed some correlations to represent the indices of germination (G) and nonfissured seeds (F) as a function of the drying variables.…”
Section: Quality Of Soybean Seedsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lacerda et al [5] studied the influence of drying variables on the quality of soybean seeds. These authors worked with a countercurrent sliding-bed dryer and proposed some correlations to represent the indices of germination (G) and nonfissured seeds (F) as a function of the drying variables.…”
Section: Quality Of Soybean Seedsmentioning
confidence: 99%
“…The grain drying process exerts a strong influence in maintaining the quality of the product during its conservation period, because it reduces the moisture content and the occurrence of biochemical reactions that degrade the product. In the literature many reports about changes in soybean seed quality during drying are available [5][6][7][8][9][10]. These studies have shown that care must be taken in any system that involves the movement of seeds, i.e., correct handling of the initial and final moisture content of the product, relative humidity, air mass flux, drying rates, and exposure time to hot air [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations